A review of applications of Analytic Hierarchy Process in operations management - Subramanian, Nachiappan; Ramanathan, Ramakrishnan (Elsevier, 2012)
The purpose of this paper is to review the literature on the applications of the Analytic Hierarchy Process (AHP) in operations management and suggest possible gaps from the point of view of researchers and practitioners. This paper systematically categorises the published literature from 1990 to 2009 in 291 peer reviewed journals articles (searched via Emerald, Ingenta, MetaPress, ProQuest, and ScienceDirect) and then reviews and analyses them methodologically. Our analysis has revealed that a significant number of AHP applications are found when problems require considerations of both quantitative and qualitative factors (e.g., socioeconomic operations decisions). AHP has been largely applied to macro (complex and real) and people (managerial–subjective) oriented problems. The most addressed decision themes are product and process design and, managing the supply chain. A majority of AHP applications are application or case study oriented and only a few papers aimed at contributing to AHP modelling before applying to practical problems. Our review has found that significant research gap exists in the application of AHP in the areas of forecasting, layout of facilities and managing stocks. This paper presents a comprehensive listing of AHP applications in operations management and develops a framework for identifying the decision areas that have better research gaps to be studied by future researchers.